1998
DOI: 10.1021/om970875v
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on the Reactivity of the Silicon−Carbon Double Bond. Mechanistic Studies of the Ene-Addition of Acetone to Reactive Arylsilenes

Abstract: Absolute rate constants for the reaction of acetone with phenylsilene, 1-methyl-1-phenylsilene, and a series of ring-substituted 1,1-diphenylsilene derivatives have been determined in polar and nonpolar solvents using nanosecond laser flash photolysis techniques. The reaction (which affords the corresponding silyl enol ether) proceeds significantly faster at 23 °C in hydrocarbon solvents than in acetonitrile in all cases, but the Hammett ρ-values defined by the data for the substituted 1,1-diphenylsilenes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 48 publications
6
56
0
Order By: Relevance
“…Silacyclobutanes are well known to yield products consistent with the formation of silene-reactive intermediates upon photolysis in solution or the gas phase, or upon pyrolysis at high temperatures (1)(2)(3)(4)(5)(6)(7)(8). These compounds have proven to be tremendously useful as photochemical precursors for transient silenes, in experiments aimed at detecting the silenes directly and studying the kinetics and mechanisms of their reactions with alcohols and other "silenophiles" (9)(10)(11)(12)(13)(14)(15)(16)(17). Photochemical silene formation proceeds with useful efficiencies from silacyclobutanes that bear alkyl, vinyl, ethynyl, silyl, and phenyl substituents at silicon, and possess UV absorption maxima between 190 and 250 nm (2,4,12,13,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Silacyclobutanes are well known to yield products consistent with the formation of silene-reactive intermediates upon photolysis in solution or the gas phase, or upon pyrolysis at high temperatures (1)(2)(3)(4)(5)(6)(7)(8). These compounds have proven to be tremendously useful as photochemical precursors for transient silenes, in experiments aimed at detecting the silenes directly and studying the kinetics and mechanisms of their reactions with alcohols and other "silenophiles" (9)(10)(11)(12)(13)(14)(15)(16)(17). Photochemical silene formation proceeds with useful efficiencies from silacyclobutanes that bear alkyl, vinyl, ethynyl, silyl, and phenyl substituents at silicon, and possess UV absorption maxima between 190 and 250 nm (2,4,12,13,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…18,20,21 The two silenes exhibit lifetimes of >5 µs in hexane and 1-4 µs in acetonitrile under these conditions and decay with mixed firstand second-order kinetics, with 1a being the longer-lived of the two. Much different behavior is observed in THF solution, where the lifetimes of the two silenes are longer, 1b is the longer-lived of the two, and their spectra are broadened and/or red-shifted as compared to hexane solution because of complexation with the ether solvent.…”
Section: Resultsmentioning
confidence: 96%
“…This behavior is also analogous to what has been observed previously for the addition of oxygen-centered nucleophiles to these two silenes. 15,18,21 In the case of oxygen-centered nucleophiles, we have recently shown that these trends are due, at least to some extent, to the effects of weak complexation of the free silene…”
Section: Discussionmentioning
confidence: 99%
“…The 1 H NMR spectrum of the compound exhibited singlets at δ 0.41 (SiCH 3 ), 2.46 (o-tolyl CH 3 ), and 3.41 (OCH 3 ) and resonances assignable to the n-propyl group (δ 0.90 (t, 2H), 0.95 (t, 3H), 1.38 (m, 2H)), and the following mass spectrum: m/z (I) = 208 (4), 193 (2), 165 (100), 151 (12), 135 (33), 119 (12), 105 (18), 91 (11), 59 (20). Both the photolysis and dark reaction mixtures also contained a second minor isomer in the same yield relative to 15 (1:8) which was tentatively identified as benzylmethylmethoxy(1-propyl)silane (16, 21%) on the basis of its mass spectrum: m/z (I) = 208 (17), 165 (15), 151 (10), 133 (12), 117 (90), 91 (30), 75 (100), 59 (30)). The latter clearly shows the fragmentation pattern expected for a benzylsilane.…”
Section: Methodsmentioning
confidence: 99%
“…Silacyclobutanes are well-known photochemical and thermal precursors to transient Si=C containing compounds ("silenes") (1)(2)(3)(4)(5)(6)(7)(8), and are tremendously useful in experiments aimed at detecting these reactive intermediates directly and studying the kinetics and mechanisms of their various characteristic reactions (9)(10)(11)(12)(13)(14)(15)(16)(17). Photochemical silene formation proceeds with useful efficiencies from silacyclobutanes bearing a wide range of substituents at silicon, ranging from compounds in which the silacyclobutane ring is the primary chromophore (e.g., 1,1-dialkylsilacyclobutanes) to those in which the lowest excited state is localized more in the substituent (e.g., 1-arylsilacyclobutanes).…”
Section: Introductionmentioning
confidence: 99%